2019
DOI: 10.1108/ijge-12-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Saudi female innovators as entrepreneurs – theoretical underpinnings

Abstract: Purpose This research is based on a theoretical interest and practical need to examine female actors as entrepreneurs and innovators. The Saudi Vision 2030 emphasizes entrepreneurship, innovation and stronger female participation in the work force. The purpose of this paper is to point to theoretical underpinnings in female entrepreneurial and innovative activity and to examine success factors for female entrepreneurial innovators in the context of the Kingdom of Saudi Arabia (KSA). Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…On the contrary, this finding may support the thesis that the situation is beginning to change, even in those countries where, until recently, women were in an unequal position (Kemppainen, 2019). Our results can confirm this because 23% of all evaluated studies came from countries in the Arabian Peninsula (10 case studies) and the Indian Peninsula (eight studies).…”
Section: Resultssupporting
confidence: 77%
“…On the contrary, this finding may support the thesis that the situation is beginning to change, even in those countries where, until recently, women were in an unequal position (Kemppainen, 2019). Our results can confirm this because 23% of all evaluated studies came from countries in the Arabian Peninsula (10 case studies) and the Indian Peninsula (eight studies).…”
Section: Resultssupporting
confidence: 77%
“…Being a woman is not a disadvantage when obtaining bank loans, as both men and women receive equal treatment (Iakovleva et al, 2013; Lituchy & Reavley, 2004). But other studies have indicated that women entrepreneurs face many challenges, including gender discrimination, work-family conflicts, financial constraints, lack of infrastructural support, unfavourable business and political environments, lack of training, and limitations due to their personality (Cho et al, 2019; Kemppainen, 2019; Nählinder, 2010).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…However, governments have aimed for improvement in this regard, particularly in the past several years. Kemppainen (2019) has shown that Saudi female entrepreneurs have chances to participate in and contribute efficiently to the labour market, mainly as a result of government efforts to implement societal and economic reforms. Similarly, Morched and Jarboui (2019) have observed that Tunisian women have launched successful enterprises as a result of their increasing awareness of market conditions and knowledge of entrepreneurial activity.…”
Section: Resultsmentioning
confidence: 99%